iPad for dummies - Baig, Edward C.; LeVitus, Bob. (Hoboken, NJ : Wiley, 2011)
This guide helps you get up to speed and on the go with Apple's latest iPad and iOS software, from surfing the Web to playing games, watching and recording videos, downloading cool apps and more.
Introduction -- Getting to know your iPad -- The Internet iPad -- The iPad at work and play -- The undiscovered iPad -- The part of tens.
Includes index.
Keywords: iPad (Computer); Tablet computers; Pocket computers -- Amateurs' manuals; Macintosh (Computer) -- Amateurs' manuals